Research progress of meliaceous limonoids from 2011 to 2021 - Luo, Jun; Sun, Yunpeng; Li, Qiurong; Kong, Lingyi (Natural product reports, 2022)
Covering: July 2010 to December 2021 Limonoids, a kind of natural tetranortriterpenoids with diverse skeletons and valuable insecticidal and medicinal bioactivities, are the characteristic metabolites of most plants of the Meliaceae family. The chemistry and bioactivities of meliaceous limonoids are a continuing hot area of natural products research; to date, about 2700 meliaceous limonoids have been identified. In particular, more than 1600, including thirty kinds of novel rearranged skeletons, have been isolated and identified in the past decade due to their wide distribution and abundant content in Meliaceae plants and active biosynthetic pathways. In addition to the discovery of new structures, many positive medicinal bioactivities of meliaceous limonoids have been investigated, and extensive achievements regarding the chemical and biological synthesis have been made. This review summarizes the recent research progress in the discovery of new structures, medicinal and agricultural bioactivities, and chem/biosynthesis of limonoids from the plants of the Meliaceae family during the past decade, with an emphasis on the discovery of limonoids with novel skeletons, the medicinal bioactivities and mechanisms, and chemical synthesis. The structures, origins, and bioactivities of other new limonoids were provided as ESI. Studies published from July 2010 to December 2021 are reviewed, and 482 references are cited. In this review, the recent progress in the discovery of new structures, bioactivities, and synthesis of limonoids from plants of the Meliaceae family have been summarized.